2011
DOI: 10.1521/jscp.2011.30.3.250
|View full text |Cite
|
Sign up to set email alerts
|

Social Support and Social Constraints Moderate the Relation between Community Violence Exposure and Depressive Symptoms in an Urban Adolescent Sample

Abstract: this longitudinal study examined whether the perceived availability of adult social support and low levels of adult social constraints in talking about violence could potentially mitigate the positive relation between community violence exposure and depressive symptoms among 216 inner-city youth (45% male, 92% african american). the majority of youth (90%) reported witnessing violence or being victimized at least once in the prior year. Perceived social support, social constraints, and depressive symptoms were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
27
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 40 publications
(32 citation statements)
references
References 43 publications
5
27
0
Order By: Relevance
“…Thus, assisting parents with their own cognitive processing and coping skills might help children by making parents more sensitive and responsive to their children’s needs. However, because youth in violence-ridden neighborhoods may have to cope with unsupportive and negative parental responses to their disclosures about violence (Dinizulu, 2014; Kaynak et al, 2011), interventions that can enhance cognitive control may be more effective than interventions addressing social conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, assisting parents with their own cognitive processing and coping skills might help children by making parents more sensitive and responsive to their children’s needs. However, because youth in violence-ridden neighborhoods may have to cope with unsupportive and negative parental responses to their disclosures about violence (Dinizulu, 2014; Kaynak et al, 2011), interventions that can enhance cognitive control may be more effective than interventions addressing social conditions.…”
Section: Discussionmentioning
confidence: 99%
“…For example, in crosssectional studies on middle-school adolescents in the United States, social support moderated the relation between poverty and academic performance (Malecki & Demaray, 2006) and the relation between victimization and internalizing-externalizing distress from bullying (Davidson & Demaray, 2007). Similarly, longitudinal studies point to the buffering role of PSS for adolescents, such as in the association between exposure to community violence and internalizing symptoms (Kaynak, Lepore, & Kliewer, 2011;Rosario, Salzinger, Feldman, & Ng-Mak, 2008), and between distress from bullying and academic achievement (Rothon, Head, Klineberg, & Stansfeld, 2011).…”
Section: Perceived Social Supportmentioning
confidence: 99%
“…As such, social constraints differs from the more general construct of social support. Previous research has found little relationship between the two constructs, and differential predictive ability when social constraints was compared with measures of social support [17,18].…”
Section: Social Constraintsmentioning
confidence: 99%